Strengthening the Financial Literacy of Sauyunan Rasa MSMEs through Simple Financial Recordkeeping Training in Cikole Village - Fanji Farman; Novy Fajriati; Ina Nusuki (Jurnal Ragam Pengabdian, 2026)
Micro, small, and medium enterprises (MSMEs) are vital to the national economy, yet many entrepreneurs in rural areas still possess limited financial literacy, particularly in financial recordkeeping and the separation of personal and business finances. This condition was identified within the “Sauyunan Rasa” MSME group in Cikole Village, Sumedang Regency, West Java, whose members operate home-based food enterprises without orderly bookkeeping. This community service activity aimed to improve participants’ understanding of basic financial literacy, develop their skills in simple recordkeeping and financial reporting based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), and foster awareness of separating personal and business finances. The activity applied a participatory training and mentoring approach using the learning-by-doing method, in which participants directly practiced recording real transactions from their own businesses, complemented by an introduction to the SIAPIK digital recording application. The level of success was measured by comparing pre-test and post-test results. The findings showed that the participants’ average score increased from 73% to 89%, an improvement of 16 percentage points, with gains across all indicators, namely understanding of financial literacy concepts, separation of personal and business finances, and simple financial recordkeeping and reporting. Qualitatively, participants who had previously managed their businesses without any records began to record transactions, calculate profit, and separate business from household finances. The activity proved effective in strengthening the financial literacy of rural MSMEs and supporting the economic independence of the partner group.